1545 Association between endocrine function and radiation exposure. (24th April 2018) - Li, Xiuting; Yu, Pengfei; Song, Haiyan; Liu, Xin; Zhao, Liangliang; Wang, Jun; Yang, Dandan; Zhu, Baoli
Abstract : Introduction: There has been a growing focus on endocrine dysfunction especially thyroid dysfunction after radiation exposure recent years. Thyroid dysfunction caused by radiation exposure or other reasons may be associated with change in BMI, weight and even induced obesity and metabolic consequences including diabetes. On the basis of above theories, we decided to observe the likely relationship of endocrine function changes within radiation exposure. Methods: A total of 1784 subjects from physical examination organisation for occupational health were investigated. Subject information was collected with a questionnaire that was carried out through interviews in the forms of face-to-face. We entered all data into a computerised database using the statistical analysis Epidata3.1, all analyses were performed by SAS 9.1.3 software. p < 0.05 was generally accepted as statistically significant. Results: The abnormal proportion of T3 and T4 in female were higher than them in male (p < 0.05). Abnormal rate of FT4 increased, accompanying with the growth of age (p < 0.05). In addition, T3 and FT3 levels may be associated with exposure time of X-ray. On the basis of this survey, abnormal rate of T3(1.4%) and FT3 (1.0%) were higher in group <3 years than that in group ≥3 years (0.3% and 0.1%, respectively. p < 0.05). We compared serum T3, T4, TSH, FT3 and FT4 levels between different degrees referred to exposure time of radiation. Subjects whose duration time longer than 3 years were likely to have higher T4 contents than those who contact less than 3 years (p < 0.05). Furthermore, normal T4 subjects and abnormal ones were researched separately. In this study, serum T4 was significantly and positively related with BMI in the T4 normal group. Within normal T4 level, T4 was a little weak positive-correlated with BMI. Conclusion: Changes in thyroid function and glucose metabolism may appear after long time exposure to radiation.